2022
DOI: 10.1149/1945-7111/ac8376
|View full text |Cite
|
Sign up to set email alerts
|

In Situ High-Temperature TEM Observation of Inconel Corrosion by Molten Chloride Salts with N2, O2, or H2O

Abstract: In situ TEM is used to understand corrosion of Inconel-625 by chloride salts (MgCl2 − NaCl − KCl) at 500-800°C in 1.0 atm inert N2 or pure O2, or hydrated salts. The isothermal corrosion rate R in inert N2 increases from 203 ± 30 μm year-1 at 700°C to 463 ± 30 μm year-1 at 800°C. An oxygen ambient causes a six-fold increase to R = 1261 ± 170 μm year-1. Salt hydration dramatically accelerates corrosion to R > 3×105 μm year-. These isothermal corrosion rates indicate that the molten chloride corrosion is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[63][64][65][66][67][68] Further research has identified through microstructure observations the role of oxygen and moisture in drastically increasing corrosion. 69,70 Additionally, the presence of secondary phases and carbides at the grain boundaries is able to induce fast propagation of localized corrosion by forming microgalvanopores that exhibit a difference in electronegativity. 54,55,[63][64][65][66] These mechanistic explanations can find potential application in the present corrosion phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…[63][64][65][66][67][68] Further research has identified through microstructure observations the role of oxygen and moisture in drastically increasing corrosion. 69,70 Additionally, the presence of secondary phases and carbides at the grain boundaries is able to induce fast propagation of localized corrosion by forming microgalvanopores that exhibit a difference in electronegativity. 54,55,[63][64][65][66] These mechanistic explanations can find potential application in the present corrosion phenomenon.…”
Section: Resultsmentioning
confidence: 99%